Lithium Alloying Potentials of Silicon as Anode of Lithium Secondary Batteries - Doh, Chil-Hoon; Oh, Min-Wook; Han, Byung-Chan (Asian Journal of Chemistry, 2013)
Using first principles density functional theory, formation energies of lithium silicides were calculated. The formation of lithium silicides such as Li1Si1, Li12Si7, Li2Si1, Li7Si2, Li15Si4 and Li22Si5 were energetically favourable with potential decreasing. Li15Si4 calculated to be more stable than Li7Si2. Differences of Si-Si bond distances between 2.383 Å of Li3.5Si as relatively good reversible range and 4.548 Å of Li3.75Si as relatively low reversibility can be correlated to reversible lithiation range. Silicon is not only electron semi-conductor but also not good lithium ion conductor. Therefore during lithiation(delithiation) silicon has multi-level lithiated silicides to show broad and complicated XRD pattern.